Human Chorionic Gonadotrophin: New Pleiotropic Functions for an “Old” Hormone During Pregnancy - Gridelet, Virginie; Perrier d'Hauterive, Sophie; Polese, Barbara; Foidart, Jean-Michel; Nisolle, Michelle; Geenen, Vincent (Frontiers in Immunology, 2020)
Human chorionic gonadotrophin (hCG) is the first specific molecule synthesized by the embryo. hcg RNA is transcribed as early as the 8-cell stage and the blastocyst produces the protein before its implantation. hCG in the uterine microenvironment binds with its cognate receptor LHCGR on the endometrial surface. This binding stimulates LIF production and inhibits IL-6 production by epithelial cells of the endometrium. These effects ensure essential help in the preparation of the endometrium for initial embryo implantation. hCG also effects angiogenic and immunomodulatory actions as reported in many articles by our laboratories and other ones. By stimulating angiogenesis and vasculogenesis, hCG provides the placenta with an adequate maternal blood supply and optimal embryo nutrition during the invasion of the uterine endometrium. The immunomodulatory properties of hCG are numerous and important for programming maternal immune tolerance towards the embryo. The reported effects of hCG on uterine NK, Treg and B cells, three major cell populations for the maintenance of pregnancy, demonstrate the role of this embryonic signal as a crucial immune regulator in the course of pregnancy. Human embryo rejection for hCG-related immunological reasons has been studied in different ways, and a sufficient dose of hCG seems to be necessary to maintain maternal tolerance. Different teams have studied the addition of hCG in patients suffering from recurrent miscarriages or implantation failures. HCG could also have a beneficial or a negative impact on autoimmune diseases during pregnancy. In this review, we will discuss the immunological impacts hCG during pregnancy and if this hormone might be used therapeutically.